Molecular cytogenetic analysis reveals the existence of two independent neo-XY sex chromosome systems in Anatolian Pamphagidae grasshoppers. Issue 1 (February 2017) - Jetybayev, Ilyas; Bugrov, Alexander; Ünal, Mustafa; Buleu, Olesya; Rubtsov, Nikolay
Abstract Background Neo-XY sex chromosome determination is a rare event in short horned grasshoppers, but it appears with unusual frequency in the Pamphagidae family. The neo-Y chromosomes found in several species appear to have undergone heterochromatinization and degradation, but this subject needs to be analyzed in other Pamphagidae species. We perform here karyotyping and molecular cytogenetic analyses in 12 Pamphagidae species from the center of biodiversity of this group in the previously-unstudied Anatolian plateau. Results The basal karyotype for the Pamphagidae family, consisting of 18 acrocentric autosomes and an acrocentric X chromosome (2n♂ = 19, X0; 2n♀ = 20, XX), was found only inG. adaliae . The karyotype of all other studied species consisted of 16 acrocentric autosomes and a neo-XY sex chromosome system (2n♂♀ = 18, neo-XX♀/neo-XY♂). Two different types of neo-Y chromosomes were found. One of them was typical for three species of theGlyphotmethis genus, and showed a neo-Y chromosome being similar in size to the XR arm of the neo-X, with the addition of two small subproximal interstitial C-blocks. The second type of the neo-Y chromosome was smaller and more heterochromatinized than the XR arm, and was typical for all Nocarodeini species studied. The chromosome distribution of C-positive regions and clusters of ribosomal DNA (rDNA) and telomeric repeats yielded additional information on evolution of these neo-XY systems. Conclusion Most Pamphagidae species in the Anatolian region were found to have neo-XY sex chromosome systems, belonging to two different evolutionary lineages, marked by independent X-autosome fusion events occurred within the Trinchinae and Pamphaginae subfamilies. The high density of species carrying neo-XY systems in the Anatolian region, and the different evolutionary stage for the two lineages found, one being older than the other, indicates that this region has a long history of neo-XY sex chromosome formation.